2001
DOI: 10.1159/000055989
|View full text |Cite
|
Sign up to set email alerts
|

Antley-Bixler Syndrome, Description of Two New Cases and Review of the Literature

Abstract: Objective: Antley-Bixler syndrome (ABS) is a rare disorder characterized by multiple malformations of cartilage and bone including multisynostotic osteodysgenesis, midface hypoplasia, choanal atresia or stenosis, femoral bowing, neonatal fractures and multiple joint contractures and, occasionally, urogenital, gastrointestinal or cardiac defects. Since the first report in 1975, at least 34 cases (including this report) have been described. We present 2 cases of congenital hydrocephalus, suggesting the cause of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
11

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
1
12
0
11
Order By: Relevance
“…Additionally, with respect to this patient's clinical situation of bilateral conductive hearing loss, chronic otitis media, and very stenotic external auditory canals, bone-anchored hearing aide (BAHA) implantation is an important consideration for amplification as compliance may improve over standard hearing aids. Second, the management of chronic otitis media is likely to be necessary in quite of a number of these patients as there has been elevated incidence between otitis media with effusion and choanal atresia [8] and as previously reported there is a 56% incidence of choanal atresia/stenosis associated with the syndrome [6]. Third, patients with ABS may have severely malformed middle ear structures including ossicular malformations, absence of the oval window, or tegmen tympani dehiscence as described in this patient.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Additionally, with respect to this patient's clinical situation of bilateral conductive hearing loss, chronic otitis media, and very stenotic external auditory canals, bone-anchored hearing aide (BAHA) implantation is an important consideration for amplification as compliance may improve over standard hearing aids. Second, the management of chronic otitis media is likely to be necessary in quite of a number of these patients as there has been elevated incidence between otitis media with effusion and choanal atresia [8] and as previously reported there is a 56% incidence of choanal atresia/stenosis associated with the syndrome [6]. Third, patients with ABS may have severely malformed middle ear structures including ossicular malformations, absence of the oval window, or tegmen tympani dehiscence as described in this patient.…”
Section: Discussionmentioning
confidence: 56%
“…The otolaryngologic manifestations of ABS have previously been reviewed, however, mention of otologic disease was limited to noting that the patient's ears were sometimes dysplastic with atresia of the external auditory canals [5]. Lee et al found that 33 of the 34 cases reviewed had dysmorphic ears [6]. Bottero et al and Lee et al found the incidence of stenotic external auditory canals in ABS as 27 and 35%, respectively [1,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 9 patients in the entire series within this category, 5 were undergoing reoperations. The association of Chiari malformation and craniosynostosis has been previously reported [8, 9, 10, 11, 12]. This association is probably related not only to mechanical distortion and compression in the posterior fossa by inadequate skull growth, but also to intracranial hypertension caused by chronic elevation of intracranial venous pressure, as proposed by Thompson et al [8], and in some patients to hydrocephalus.…”
Section: Discussionmentioning
confidence: 81%
“…Antley-Bixler syndrome (ABS, OMIM 207410) is a congenital malformation syndrome characterized mainly by craniosynostosis and radiohumeral synostosis [Bottero et al, 1997;Lee et al, 2001]. There are two types of ABS: an autosomal dominant form and an autosomal recessive form.…”
mentioning
confidence: 99%